A Green Raman Spectroscopic Assay Method for The Quantification of Tranexamic Acid in Pharmaceutical Formulations - Singh, P. S.; Lokhande, R.S.; Kochrekar, D. A. (International Journal of Experimental Research and Review, 2023)
Tranexamic acid (TXA) is a widely used antifibrinolytic agent that is used to prevent and treat excessive bleeding. Current analytical methods for TXA are often time-consuming and require the use of toxic solvents. Raman spectroscopy has the ability to measure TXA because it is a fast and non-destructive analytical method. This research established and validated a green Raman spectroscopic test for TXA measurement. There was no need for harmful solvents because the technique relied on a basic aqueous solution of TXA. Results demonstrated that the technique was linear across the 0.7% to 13.0% concentration range. The method was also shown to be accurate, with results comparable to the orthogonal techniques. The green Raman spectroscopic assay method was applied to the quantification of TXA in pharmaceutical formulations. The results obtained were comparable to those obtained using reference methods. To quantify TXA quickly and accurately, one can use the green Raman spectroscopic test. Since no harmful chemicals are needed for the procedure, it is also eco-friendly. Method has the potential to be used in a variety of settings, including pharmaceutical quality control and research laboratories.